Primary brain T-cell lymphoma in a cat - Sant’Ana, Fabiano J. F. de; Reis Junior, Janildo L.; Brown, Corrie C.; Langohr, Ingeborg M.; Barros, Claudio S. L. (Brazilian Journal of Veterinary Pathology, 2010)
A 10-year-old, female, mixed-breed cat was presented for necropsy with history of incoordination, circling and nystagmus or fixed gaze. Grossly, slight asymmetry was observed in the right telencephalic hemisphere, mainly in the pyriform lobe. Histologically, sheets of small round neoplastic cells were observed in the pons, midbrain, thalamus and in the subcortical white matter of the parietal, occipital and pyriform lobes. Neoplastic cells were strongly labeled with anti-CD3 antibody by means of immunohistochemistry. Anti-BLA36, CD79a and MAC387 failed to label the neoplastic cells. Based on the histopathological findings and on the immunohistochemical results, a diagnosis of primary brain T-cell lymphoma was made.